2017
DOI: 10.1080/15476286.2017.1408765
|View full text |Cite
|
Sign up to set email alerts
|

A DNA segment encoding the anticodon stem/loop of tRNA determines the specific recombination of integrative-conjugative elements in Acidithiobacillus species

Abstract: Horizontal gene transfer is crucial for the adaptation of microorganisms to environmental cues. The acidophilic, bioleaching bacterium Acidithiobacillus ferrooxidans encodes an integrative-conjugative genetic element (ICEAfe1) inserted in the gene encoding a tRNA. This genetic element is actively excised from the chromosome upon induction of DNA damage. A similar genetic element (ICEAca.2) is also found in an equivalent position in the genome of Acidithiobacillus caldus. The local genomic context of both mobil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…This region, in addition to integrase genes and IS elements, also contained several tRNA genes. The role of tRNA genes as target loci for the insertion of horizontally acquired DNA sequences has been extensively documented ( Schmidt and Hensel, 2004 ; Castillo et al, 2017 ). The increasing evidence that Vibrionaceae species are indeed prone to gain foreign DNA by natural transformation ( Sun et al, 2013 ; Antonova and Hammer, 2015 ; Metzger and Blokesch, 2016 ), suggests that some of these variable DNA sequences might have been taken from the environment and inserted into the P. damselae subsp.…”
Section: Discussionmentioning
confidence: 99%
“…This region, in addition to integrase genes and IS elements, also contained several tRNA genes. The role of tRNA genes as target loci for the insertion of horizontally acquired DNA sequences has been extensively documented ( Schmidt and Hensel, 2004 ; Castillo et al, 2017 ). The increasing evidence that Vibrionaceae species are indeed prone to gain foreign DNA by natural transformation ( Sun et al, 2013 ; Antonova and Hammer, 2015 ; Metzger and Blokesch, 2016 ), suggests that some of these variable DNA sequences might have been taken from the environment and inserted into the P. damselae subsp.…”
Section: Discussionmentioning
confidence: 99%
“…In 16 of these 18 instances, an integrase or a transposase gene also was present, suggesting that HGT events that occur at the site of a tRNA gene may occur via a different mechanism compared to the majority of HGT events. In fact, Castillo et al [19] described a mobile element in Acidithiobacillus that integrates at the site of a tRNA gene. Thus, tRNA genes may be sites that are specifically targeted by some integrases and recombinases.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to their vital role in protein synthesis and synthetic biology applications, tRNAs are also involved in cellular processes beyond translation. These processes include lipid aminoacylation [9] and bacterial conjugation [10]. The contributions to the special issue in this area also focused on the role of tRNA modifications in wobble decoding [11] and bacterial cell death [12].…”
Section: Trna Evolution and Modification In Microorganismsmentioning
confidence: 99%
“…Alamos et al found that the acidophilic bacterium Acidithiobacillus ferrooxidans encodes 36 of its 95 tRNAs in an integrative-conjugative genetic element [13]. Indeed, Castillo et al show that the integrases encoded in the conjugative element recognize the anticodon stem loop region in the tRNA gene for active and site-specific recombination [10].…”
Section: Trna Evolution and Modification In Microorganismsmentioning
confidence: 99%